Exploring the anti-inflammatory properties of zingiber officinale var. rubrum in preventing polycystic ovary syndrome: In Silico and in Vivo studies - Mudrikatin, Siti; Nugraha, Jusak; Sujarwo, Sri A.; I’tishom, Reny; Kurnijasanti, Rochmah (Edelweiss Applied Science and Technology, 2025)
The increasing incidence of polycystic ovary syndrome (PCOS), will cause oxidative stress due to hyperglycemia, which subsequently elevates expression levels of proinflammatory cytokines, particularly tumor necrosis factor-alpha (TNF-α), contributing to a marked rise in infertility, observed in up to 89.6% cases. This study aimed to investigate the potential of Zingiber officinale var. rubrum in preventing PCOS. The in vivo laboratory-based experimental study utilized Rattus norvegicus, with 5 rats per group, divided into five experimental groups. The intervention consisted of Zingiber officinale var. rubrum extract for PCOS prevention. Statistical analysis was performed using one-way ANOVA. The silico study began with the preparation of activator ligands 6-Shogaol and 6-Gingerol, along with target receptors TNF-α and KEP1, NF-ҝβ. The in silico analysis showed that compounds from Zingiber officinale var. rubrum exhibited binding interactions with TNF-α at sites similar to the control ligands, showing greater affinity compared to interactions with SOD. The in vivo analysis showed that significantly elevated TNF-α expression levels and induced folliculogenesis abnormalities characteristic of PCOS (p < 0.05) compared to negative controls. The findings indicate that the bioactive compounds 6-Shogaol and 6-Gingerol present in Zingiber officinale var. rubrum may exert preventive effects against PCOS by modulating inflammatory pathways.